2006
DOI: 10.1124/jpet.106.103143
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate 5 Receptor Antagonism Is Associated with Antidepressant-Like Effects in Mice

Abstract: Antidepressant-like effects of metabotropic glutamate (mGlu)5 receptor antagonists have been reported previously. We now provide definitive identification of mGlu5 receptors as a target for these effects through the combined use of selective antagonists and mice with targeted deletion of the mGlu5 protein. In these experiments, the mGlu5 receptor antagonists 2-methyl-6-(phenylethynyl)-pyridine (MPEP) and the more selective and metabolically stable analog 3-[(2-methyl-1,3-thiazol-4-yl)ethynyl]-pyridine (MTEP) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 34 publications
7
102
1
1
Order By: Relevance
“…Both compounds reduced immobility times in despair models, such as forced swim and tail suspension tests [88][89][90]. The antidepressant effects of MPEP in the forced swim test were no longer observed in knockout mice lacking mGlu5 receptors [88], indicating that these compounds exerted their effects via the mGlu5 receptor.…”
Section: Mglu5 Receptor Antagonistsmentioning
confidence: 94%
See 1 more Smart Citation
“…Both compounds reduced immobility times in despair models, such as forced swim and tail suspension tests [88][89][90]. The antidepressant effects of MPEP in the forced swim test were no longer observed in knockout mice lacking mGlu5 receptors [88], indicating that these compounds exerted their effects via the mGlu5 receptor.…”
Section: Mglu5 Receptor Antagonistsmentioning
confidence: 94%
“…Both compounds reduced immobility times in despair models, such as forced swim and tail suspension tests [88][89][90]. The antidepressant effects of MPEP in the forced swim test were no longer observed in knockout mice lacking mGlu5 receptors [88], indicating that these compounds exerted their effects via the mGlu5 receptor. Moreover, subchronic administration of MPEP or MTEP attenuated abnormal behaviors (learning deficits in a passive avoidance paradigm or locomotor hyperactivity in a novel environment) induced by olfactory bulbectomy [89,91].…”
Section: Mglu5 Receptor Antagonistsmentioning
confidence: 94%
“…However, some investigators have reported that multiple dosing procedures with these compounds produces increases efficacy in the anxiolytic, antidepressant or anti-addictive effects as compared with acute administration (Backstrom et al, 2004;Cowen et al, 2005;Klodzinska et al, 2004;Li et al, 2006;Nordquist et al, 2007;Pilc et al, 2002). This raises the possibility that changes in gene expression may underlie some of the behavioral effects of MPEP and/or MTEP following repeated exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, to begin with, attempts to investigate the potential antidepressant-like effect of the antagonists of mGlu 5 receptors were undertaken. As shown in Table 2 the selective orthosteric antagonist for this receptor, MPEP (Gasparini et al, 1999) and its derivative MTEP (Cosford et al, 2003), were active in the forced swim test in both rats and mice, and in the tail suspension test in mice (Belozertseva et al, 2007;Li et al, 2006;Palucha et al, 2005;Pilc et al, 2002;TatarczyƄska et al, 2001). Moreover, in the olfactory bulbectomy model of depression it was shown that chronic administration of those substances evoked behavioural effects similar to those observed after the administration of ADDs administration (Palucha et al, 2005;Pilc et al, 2002;Wieronska et al, 2005 in the hippocampus of the rat brain, which remains in line with the neurotrophic theory of depression (Legutko et al, 2006 The antidepressant effects could be evoked not only after administration of mGlu 5 receptor antagonists, but also after blockade of mGlu 1 receptor subtype, the second representative of group I mGlu receptors, as its antagonist EMQMCM was effective in the tail suspension and forced swim test in mice (Belozertseva et al, 2007).…”
Section: The Role Of Group I Mglu Receptors In the Mechanism Of Actiomentioning
confidence: 99%